Strategi Manajemen Digitalisasi: Sebagai Aksi Integrasi Sistem Informasi Keagamaan - Andi Sugiharta (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes how one of the missions of the Indonesian Ministry of Religious Affairs for 2025-2029 is to "improve the understanding and practice of moderate and welfare-oriented religious teachings" in conjunction with the Ministry of Religious Affairs' 2024 outlook program, namely winning the digital competition can be realized as a form of recommendation at the 2024 Ministry of Religious Affairs National Working Meeting (Rakernas). The purpose of this policy paper is to discuss the potential of digitalization management as an action plan and the Ministry of Religious Affairs' strategy in utilizing it for the integration of digital-based religious information systems. With a qualitative approach, this policy paper emphasizes the descriptive-analytical method by analyzing secondary data from various sources, such as scientific journals, news articles, and official documents of the Ministry of Religious Affairs. In general, the results/data of this policy analysis show that digitalization management has proven effective in spreading messages of preaching and education to the broader community, especially the younger generation who are active in the digital world. The Ministry of Religious Affairs has a great opportunity to utilize digitalization management as a tool to strengthen religious moderation, increase religious literacy, and build a positive image of religion in the digital era. The alternative policy is to develop interesting and innovative religious information integration content, involving all aspects of the Ministry of Religion's integration utilizing popular digital platforms and collaborating with influencers and religious communities.